On Effective Leadership Across Domains, Cultures, and Eras - Chandler, G. (Jepson Studies in Leadership, 2013)
Using case studies from a wide range of fields and historical settings, On Effective Leadership seeks to explain why some leaders are effective, why many are not, and why only a very few are exceptional.